Analisis Yuridis Pengaruh Hukum Positif Indonesia Terhadap Adat Lipas Di Desa Betteng - Habsy, Muhammad Ahmad (Hukum dan Masyarakat Madani, 2022)
This study aims to determine the effect of positive Indonesian law on Lipas adat in Betteng Village, as well as to determine the factors that influence the existence of Lipas adat. Furthermore, the research method used in this study is related to the juridical analysis of the influence of positive Indonesian law on the Limas custom in Betteng. The type of research is empirical juridical. The results of this study indicate that in the view of Islamic law, most of them adhere to Islam, which is generally known that in this religion there is no word for ex-parents or ex-children. So basically, in the view of Islam, the cockroach tradition is not enforced, whose existence is based on emotion. Indonesian positive law that contradicts Lipas custom: The cockroach custom violates the Law of the Republic of Indonesia Number 35 of 2014 concerning Amendments to Law Number 23 of 2001 concerning Child Protection, The cockroach custom is not in accordance with the prevailing religion, The cockroach custom violates the Law of the Republic of Indonesia Number 39 of 1999 concerning Human Rights, the cockroach custom does not have a negative impact on Law no. 1 of 1974 concerning Marriage.